Distortionary tax instruments and implementable monetary policy - Luigi Marattin; Massimiliano Marzo; Paolo Zagaglia (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2009)
We introduce distortionary taxes on consumption, labor and capital income into a New Keynesian model with Calvo pricing and nominal bonds. We study the relation between tax instruments and optimal monetary policy by computing simple rules for monetary and fiscal policy when one tax instrument at a time varies, while the other two are fixed at their steady-state level. The optimal rules maximize the second-order approximation to intertemporal utility. Three results emerge: (a) when prices are sticky, perfect inflation stabilization is optimal independently from the tax instrument adopted; (b) the optimal degree of responsiveness of monetary policy to output varies depending on which tax instrument induces fluctuations in the average tax rate; (c) when prices are flexible, fiscal rules that prescribe unexpected variations in the price level to support debt changes are always welfare-maximizing.
Keywords: E52; E61; E63; 330